2021
DOI: 10.1111/rda.13985
|View full text |Cite
|
Sign up to set email alerts
|

Tubular ectasia of the rete testis in an Angus bull

Abstract: An 18‐month‐old Angus bull presented to Auburn University College of Veterinary Medicine for a routine breeding soundness evaluation and lameness evaluation. He was classified as deferred potential breeder due to a lameness and was donated to the university. Following treatment, the bull's lameness resolved. He passed the breeding soundness examination in accordance with the Society for Theriogenology standards. However, avascular dilated areas at the level of the mediastinum testis of the right testicle were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Waters et al . 16 showed that some cases of OA showed rete testis ectasia. Moreover, it was shown that rete testis development was affected by the endocrine system 17 , 18 and several diseases that cause NOA.…”
Section: Introductionmentioning
confidence: 99%
“…Waters et al . 16 showed that some cases of OA showed rete testis ectasia. Moreover, it was shown that rete testis development was affected by the endocrine system 17 , 18 and several diseases that cause NOA.…”
Section: Introductionmentioning
confidence: 99%